Research on the tourism service quality evaluation of Gongbei Lingnan community under the perspective of SERVQUAL theory - Liu, Jing; Kuai, Xinru; Wang, Pohsun (Frontiers in Sustainable Cities, 2025)
The Lingnan community, located between Macau and Zhuhai City in China, serves as a connecting port community that attracts a growing number of tourists for leisure and business. The Lingnan community faces the challenge of improving tourism services to meet the ever-increasing needs of tourists with the continuous growth of tourists. Currently, the community’s tourism service facilities are relatively scarce, and the service quality needs to be improved. Hence, improving tourists’ satisfaction with Lingnan tourism services is essential. The SERVQUAL Model is utilized in this research to assess the satisfaction of tourism services in the Lingnan community. The data were collected from 254 tourists who visited the Lingnan community. After passing reliability and validity tests, factor analysis was used to determine the weights of the primary indicators, followed by entropy weight calculations to measure the weights of secondary indicators further, and finally presented as an IPA matrix. The survey results show that the second-level dimension factors under the tangible, reliability, assurance, and security dimensions significantly impact tourist satisfaction. The study shows that tourist satisfaction predominantly affects the sustainable development of community tourism, so the community must focus on ensuring better service quality. Enhancing the attractiveness of Lingnan community tourism is conducive to the joint development of the tourism industry in Zhuhai and Macau but also has essential significance in strengthening the friendship between Zhuhai and Macau.